The Cardinal Protectors of the Spanish monarchy (XVI-XVII centuries) - Bénichou, Léa (Cuadernos de Historia Moderna, 2021)
This study focuses on the functioning and political significance of the figure of the cardinal protectors of the Hispanic kingdoms in Rome at the time of the reign of Felipe II and Felipe III, based on the study of the documentation of the Spanish monarchy embassy to the Holy See, which is conserved in the General Archive of Simancas and in the National Historical Archive of Spain. The work here was not only to identify the different cardinals holding the role of protectors but also to highlight the mechanisms that supported their appointment, including the interim protectors and the vice-protectors or "pro-protectors". Moreover, this work explores the political and diplomatic role that cardinal protectors played beyond their official task, as, for example, the recommendation and presentation in consistory, to the Holy See, of the candidates proposed by the monarch capable to occupy an ecclesiastical vacant and benefit in the sphere of the monarch’s royal patronage.
Keywords: Cardinal Protectors of the Crown; Spanish Embassy in Rome; Spanish monarchy; XVI-XVII centuries